Synthesis and spectroscopic characterization of polythiophene containing pendant oligoaniline groups - Proń, A.; Dufour, B.; Rannou, P.; Zagórska, M.; Buga, K.; Kulszewicz-Bajer, I. (Polimery, 2022)
We report on a new class of hybrid conjugated polymers in which side oligoaniline groups are attached to the poly(2,5- thienylene) main chain. Soluble polymers of this type can be obtained by copolymerization of 3-alkylthiophene with thiophene functionalized at the position 3 with oligoanilines (aniline dimer and aniline tetramer). The resulting polymers are electroactive and may be electrochemically doped via anodic oxidation similarly as classical polythiophenes. In addition their side oligoaniline chains can be selectively doped via protonation (doping of acid-base type). Spectroscopic properties of undoped polymers as well as spectroscopic consequences of the doping process are discussed in details. Poly(3-alkylthiophene-co-3-oligoanilinethiophene)s are promising materials for the fabrication of polymeric solar cells since in addition to their electron donating properties their absorption spectrum covers a large range of the visible spectrum.